2021
DOI: 10.3390/md19020076
|View full text |Cite
|
Sign up to set email alerts
|

Small-Scale Preparation of Fluorescently Labeled Chemical Probes from Marine Cyclic Peptides, Kapakahines A and F

Abstract: A number of bioactive marine natural products have been isolated so far, but it is still difficult to disclose their modes of action. In this study, we prepared fluorescently labeled chemical probes from the cytotoxic marine cyclic peptides kapakahines A (1) and F (2) to visualize their localization as the first step of the study of their modes of action. We used fluorescent dyes 3a or 3a/b (a 1:1 mixture of 3a and 3b) whose terminal N-hydroxysuccinimide (NHS) group can react with the free amino groups of kapa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…In our previous report [ 10 ], the fluorescently labeled kapakahine A in HeLa cells was not found to subcellularly localize with the endoplasmic reticulum or the Golgi apparatus; however, a fluorescent probe of kapakahine E was shown to localize with the Golgi apparatus [ 3 ]. To investigate the subcellular localization of the kapakahine A fluorescent probe in P388 cells—towards which kapakahine A shows cytotoxicity—co-staining with Kap A-5FL ( 2 ) and MitoTracker was carried out.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous report [ 10 ], the fluorescently labeled kapakahine A in HeLa cells was not found to subcellularly localize with the endoplasmic reticulum or the Golgi apparatus; however, a fluorescent probe of kapakahine E was shown to localize with the Golgi apparatus [ 3 ]. To investigate the subcellular localization of the kapakahine A fluorescent probe in P388 cells—towards which kapakahine A shows cytotoxicity—co-staining with Kap A-5FL ( 2 ) and MitoTracker was carried out.…”
Section: Resultsmentioning
confidence: 99%
“…Rocha et al synthesized a fluorescent probe comprising kapakahine E conjugated with coumarin and found that the fluorescent probe localized to the Golgi apparatus in PC-3M prostate carcinoma cells [ 9 ]. In a previous study, we prepared a fluorescent probe of kapakahine A [Kap A-5FL ( 2 )] by direct coupling with an FITC derivative with an active ester linker [ 10 ]. Co-localization analysis of Kap A-5FL ( 2 ) and Golgi-binding lectin HPA, or concanavalin A (endoplasmic reticulum marker) in HeLa cells, showed that Kap A-5FL does not localize in the Golgi apparatus or endoplasmic reticulum.…”
Section: Introductionmentioning
confidence: 99%
“…Fluorescently labelled kapakahine A has been used to stain P388 murine leukemia cells and HeLa human cervical cells. 131…”
Section: Natural Products Linked By Tryptophan Substitutionmentioning
confidence: 99%
“…Kapakahines (structures not shown), a large family of cyclic peptides containing an α-carboline skeleton, were isolated from Cribrochalina olemda (marine sponge) (Yeung et al, 1996;Nakao et al, 2003). They were often studied as fluorescently labeled chemical probes (Rocha et al, 2015;Kamihira and Nakao, 2021) or anti-malarial agents (Goto et al, 2021).…”
Section: Natural Occurring α-Carbolinesmentioning
confidence: 99%